Constructing an optional ICSID appeals facility in sustainable development perspective - Zhang, Xi; Ab Rahman, Rozanah; Ambaras Khan, Hanna (Izdatel'stvo Statut, 2023)
Given the growing interconnection between international investment and sustainable development, theres an escalating need to rebalance interests in international investment relations. Currently, the International Center for Settlement of Investment Disputes (ICSID), one of the most effective investor-state investment dispute resolution tools, has an internal arbitral award annulment procedure that fails to achieve a balance between the values of fairness and efficiency in arbitration. This article aims to propose ideas for establishing an ICSID arbitration appeals mechanism, employing qualitative methodologies like desk and literature research. The findings highlight the difficulty of mandating an ICSID appeal facility. Thus, a practical approach involves introducing an optional ICSID appeals mechanism with increased procedural flexibility for state parties. Such an approach is more likely to garner consensus among ICSID members and contribute to ensuring security and predictability in a new international investment framework geared towards sustainable development.